PELATIHAN KETANGGUHAN UNTUK MENINGKATKAN KESEJAHTERAAN PSIKOLOGIS PENGURUS UNIT KEGIATAN MAHASISWA (UKM) DI UNIVERSITAS SURABAYA - Widhigdo, Jessica Christina; Ahuluheluw, Joshua Michael; Pandjaitan, Lena Nessyana (Konsorsium Psikologi Ilmiah Nusantara (KPIN))
Abstract ? Involvement in various organizational activities may positively or negatively affect students? psychological well-being (PWB). Hardiness, which involves commitment, control, and openness towards challenges, is the psychological trait that is considered essential for an effective problem solving, and is believed to be necessary in order to take the most positive advantage of organizational involvement. The present study aimed to examine the changes in the PWB scores of students who were involved in organizational activities after undergoing hardiness training; it also aims at exploring the relationship between hardiness and PWB. Participants were 20 university students aged 18 to 22 years old who were involved in student organizations. Quantitative data analysis was conducted using Wilcoxon and Spearman nonparametric tests. Results showed that there was a significant increase in the PWB scores after participating in the hardiness training. The study also found a positive correlation between hardiness and PWB. Abstrak ? Kegiatan berorganisasi dapat membawa dampak positif dan negatif terhadap kesejahteraan psikologis mahasiswa (psychological well being; PWB). Kepribadian tangguh yang terdiri dari komitmen, kontrol, dan terbuka terhadap tantangan dibutuhkan untuk menghadapi masalah dengan efektif, sehingga dapat memberi manfaat positif dalam keikutsertaan berorganisasi. Penelitian ini bertujuan untuk mengetahui perubahan PWB mahasiswa setelah mengikuti pelatihan ketangguhan dan mengeksplorasi keterkaitan antara ketangguhan dan PWB. Partisipan ialah 20 mahasiswa (18-22 tahun) yang terlibat sebagai pengurus UKM. Analisis data kuantitatif dilakukan menggunakan analisis non-parametrik Wilcoxon dan Spearman. Hasil penelitian ini menemukan bahwa terdapat peningkatan skor PWB pada pengurus UKM setelah mengikuti pelatihan ketangguhan, dan terdapat korelasi positif antara ketangguhan dan PWB.